The Pathobiology of Neisseria gonorrhoeae Lower Female Genital Tract Infection - Edwards, Jennifer L.; Butler, Emily K. (Frontiers in Microbiology, 2011)
Infection and disease associated with Neisseria gonorrhoeae, the gonococcus, continue to be a global health problem. Asymptomatic and subclinical gonococcal infections occur at a high frequency in females; thus, the true incidence of N. gonorrhoeae infections are presumed to be severely underestimated. Inherent to this asymptomatic/subclinical diseased state is the continued prevalence of this organism within the general population, as well as the medical, economic, and social burden equated with the observed chronic, disease sequelae. As infections of the lower female genital tract (i.e., the uterine cervix) commonly result in subclinical disease, it follows that the pathobiology of cervical gonorrhea would differ from that observed for other sites of infection. In this regard, the potential responses to infection that are generated by the female reproductive tract mucosa are unique in that they are governed, in part, by cyclic fluctuations in steroid hormone levels. The lower female genital tract has the further distinction of being able to functionally discriminate between resident commensal microbiota and transient pathogens. The expression of functionally active complement receptor 3 by the lower, but not the upper, female genital tract mucosa; together with data indicating that gonococcal adherence to and invasion of primary cervical epithelial cells and tissue are predominately aided by this surface-expressed host molecule; provide one explanation for asymptomatic/subclinical gonococcal cervicitis. However, co-evolution of the gonococcus with its sole human host has endowed this organism with variable survival strategies that not only aid these bacteria in successfully evasion of immune detection and function but also enhance cervical colonization and cellular invasion. To this end, we herein summarize current knowledge pertaining to the pathobiology of gonococcal infection of the human cervix.